Strategi Peningkatan Pendapatan Asli Daerah (PAD) Tempat Pelelangan Ikan (TPI) Pomako Kabupaten Mimika - Nusa, Yahya; Berkat, Yermias J (STIE Jambatan Bulan, 2022)
This study aims to increase the Fisheries sector's Regional Native Income (PAD) from the Pomako Fish Auction Place (TPI). The method used is descriptive. Analysis tools using SWOT analysis is the systematic identification of various factors to formulate a company's strategy based on maximizing strengths and opportunities and minimizing weaknesses and threats. The results of this study show that the ST strategy is produced or supports verified strategies in the form of socialization, enforcement of PERDA and PERKADA as well as the formation of an integrated team